The use of case marking for predictive processing in second language Japanese - MITSUGI, SANAKO; MACWHINNEY, BRIAN (Bilingualism (Cambridge, England), 2016)
Research on processing in English has shown that verb information facilitates predictive processing. Because Japanese verbs occur at the ends of clauses, this information cannot be used to predict the roles of preceding nominals. Kamide, Altmann and Haywood (2003) showed that native Japanese speakers use case markers to predict forthcoming linguistic items. In the present study, we investigated whether second language learners of Japanese demonstrate such predictive effects when processing sentences containing either the monotransitive or ditransitive constructions. A visual-world paradigm experiment showed that, although native speakers generated predictions for syntactic outcomes, the learners did not. These findings underscore the usefulness of morphosyntactic information in processing Japanese and indicate that learners fail to make full use of case markers to generate expectations regarding syntactic outcomes during online processing. Learners may rely on nonlinguistic information to compensate for this deficit in syntactic processing.